2018
DOI: 10.1021/acsami.8b03275
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism Control by Doping in LaAlO3/SrTiO3 Heterointerfaces

Abstract: Magnetic two-dimensional electron gases at the oxide interfaces are always one of the key issues in spintronics, giving rise to intriguing magnetotransport properties. However, reports about magnetic two-dimensional electron gases remain elusive. Here, we obtain the magnetic order of LaAlO/SrTiO systems by introducing magnetic dopants at the La site. The transport properties with a characteristic of metallic behavior at the interfaces are investigated. More significantly, magnetic-doped samples exhibit obvious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…For centuries, researchers have been devoting their lifetime efforts to making electronics cheaper, more compact, and more energy-efficient. [1][2][3][4][5][6][7][8][9] A good example is that spintronics applications are the minimization of electronic devices. [1][2][3]10] Here, spins, instead of electrons, serve as information storage media, as well as logical and information processing devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For centuries, researchers have been devoting their lifetime efforts to making electronics cheaper, more compact, and more energy-efficient. [1][2][3][4][5][6][7][8][9] A good example is that spintronics applications are the minimization of electronic devices. [1][2][3]10] Here, spins, instead of electrons, serve as information storage media, as well as logical and information processing devices.…”
Section: Introductionmentioning
confidence: 99%
“…For centuries, researchers have been devoting their lifetime efforts to making electronics cheaper, more compact, and more energy‐efficient . A good example is that spintronics applications are the minimization of electronic devices .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, manipulating magnetism in semiconductors is the foundation of spintronics. As nonmagnetic materials, hybrid perovskites were recently integrated into spintronic devices and used as a spacer between ferromagnetic (FM) electrodes. It was reported that the magnetic field can assist the preparation of perovskite films, enhancing the performance of PSC . Moreover, the magnetic field effect is significant in perovskites because of the strong spin–orbit coupling (SOC) brought by the heavy atoms (Pb, I) in their building block. , In a recent work, Zhang et al attributed the influence of magnetic field on photoelectric characteristics to the spin-mixing of photogenerated electron–hole pairs with different g -factors .…”
mentioning
confidence: 99%
“…The ever-rising demand for smaller, faster, lower-power consumption spintronic devices, where the spin is the information carrier, keeps increasing rapidly. The way of regulating spins in these devices is crucial; however, the traditional current-driven methods have high-energy consumption. Moreover, the voltage control of magnetism through the piezo/ferroelectric layer , or ionic liquid still suffers from problems such as material growth, substrate clamping effect, interfacial chemical reactions, long response time, and so forth. Recently, researchers have developed photovoltaic (PV) control of magnetism in PV/ferromagnetic (FM) metals or oxide heterojunctions, where the photo-induced electrons are generated in the PV layer, transferred into the FM layer, and then changed the FM properties via shifting its Fermi level. Compared with other magnetic regulation methods, the PV control of magnetism is fast, energy-efficient, clean, and easy to integration.…”
Section: Introductionmentioning
confidence: 99%